2012
DOI: 10.1016/j.biomaterials.2011.11.065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitronectin on the differentiation of embryonic stem cells in a 3D culture system

Abstract: While stem cell niches in vivo are complex three-dimensional (3D) microenvironments, the relationship between the dimensionality of the niche to its function is unknown. We have created a 3D microenvironment through electrospinning to study the impact of geometry and different extracellular proteins on the development of cardiac progenitor cells (Flk-1(+)) from resident stem cells and their differentiation into functional cardiovascular cells. We have investigated the effect of collagen IV, fibronectin, lamini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 54 publications
2
47
0
Order By: Relevance
“…Using a live/dead cytotoxicity assay, we can see in Figure 1 that the environment of the hydrogel supports mES cell growth. We did observe a slower proliferation rate (data not shown) of cells encapsulated within the hydrogel as compared to cells maintained on gelatin-(for control) and collagen IV-coated dishes in 2D culture conditions, yet this was similar to the proliferation rates we observed previously when cells were cultured on nanofibrous scaffolds [2,4]. Additionally, we observed different morphologies of cells in 2D culture versus 3D culture.…”
Section: Cells Maintained In Ha-hydrogel Survivesupporting
confidence: 87%
See 3 more Smart Citations
“…Using a live/dead cytotoxicity assay, we can see in Figure 1 that the environment of the hydrogel supports mES cell growth. We did observe a slower proliferation rate (data not shown) of cells encapsulated within the hydrogel as compared to cells maintained on gelatin-(for control) and collagen IV-coated dishes in 2D culture conditions, yet this was similar to the proliferation rates we observed previously when cells were cultured on nanofibrous scaffolds [2,4]. Additionally, we observed different morphologies of cells in 2D culture versus 3D culture.…”
Section: Cells Maintained In Ha-hydrogel Survivesupporting
confidence: 87%
“…However, the role of the ECM within the cardiovascular progenitor cell niche is still relatively unknown. Recently, it has been shown that the addition of ECM proteins to an in vitro culture contributes to the induction of a CPC population [2,4]. Here, we demonstrate that the addition of a 3D element further enhances that induction.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…A feeder layer of embryonic fibroblast cells (MEFCs) or medium that contains the anti-differentiation cytokine leukemia inhibitory factor (LIF) are used. Withdrawal of LIF from the medium or removal of the ESCs from the feeder layer results in the formation of ‘embryoid bodies’, in which all 3 germ layers (endoderm, mesoderm, and ectoderm) are present [56,57,58,59,60]. …”
Section: Stem Cell Classification Based On Originmentioning
confidence: 99%